Foreign Direct Investment and Economic Growth: Literature from 1980 to 2018 - Lasbrey, Anochiwa; Enyoghasim, Michael; Tobechi, Agbanike; Uwajumogu, Nkechi; Chukwu, Basil; Kennedy, Ololo (International Journal of Economics and Financial Issues, 2018)
Foreign direct investment (FDI) is argued to play a pivotal role in accelerating economic growth (EG) of a host country especially in developing and Organization for Economic Co-operation and Development countries. The papers reviewed have a good representation of diverse empirical works of over three decades. It examines the relationship between FDI and EG from 1980 up to 2018. The result is mixed but heavily skewed towards significantly positive effect, but in some cases it is negative or even null of FDI on EG. We also find market size, economic freedom, availability of internet as very important determinants for FDI location and for it to create positive impact on overall EG. Keywords: Economic Growth, Foreign Direct Investment, Literature Review JEL Classifications: 040, 047